AB0725 FACTORS ASSOCIATED WITH RADIOGRAPHIC SPINAL INVOLVEMENT IN SPONDYLOARTHRITIS. (2nd June 2020) - Slouma, M.; Rahmouni, S.; Dhahri, R.; Gharsallah, I.; Boussetta, N.; Gueddich, H.; Ajili, F.; Metoui, L.; Louzir, B.
Abstract : Background: Spondyloarthritis (SpA) is characterized by significant radiographic changes in the spine. The structural spine damage can be assessed using several scorings such as the Bath AS Radiology Index (BASRI) and the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS). Objectives: We aimed to identify factors associated with structural damage in the spine using these scores. Methods: We conducted a cross-sectional study including patients with SpA diagnosed according to the assessment of Spondyloarthritis International Society criteria. To assess the radiographic involvement of the spine, we used the mSASSS, the BASRI-spine (BASRI-S), the BASRI-lumber (BASRI-L) and the BASRI-cervical (BASRI-C). Disease activity was assessed using the BASDAI and ASDAS-CRP. Results: Among the 112 patients, 72.32% were men. The mean age was 43.78 ± 12, 91 years. The mean age at diagnosis was 37.8 ± 13.45 years. The diagnostic delay of 37, 8 ± 46 months. Forty-nine patients were smockers (43.8%). The mean BASDAI score and ASDAS–CRP score were 4.04 ± 1.99 and 3.30 ± 0.87. The mean ESR and CRP were 36.21 ± 27 (mm/H) and 31.28 ± 47.25 mg/L The mean BASRI-S was 3, 99 ± 21, 96 and the mean mSASSS was 10, 26 ± 15, 41. Twenty-five patients (22.3%) had non-radiographic axial SpA. Men had higher BARSI-L (1.36 vs 0.7, p= 0.045) and BASRI-S (4.3 vs 3.09; p=0.047) than women. Moreover, smokers' patients had higher mSASSS (14.07 vs 7.02; p=0.031), BASRI-C (1.23 vs 0.62; p=0.031), and BASRI-S (4.82 vs 3.35; p= 0.009) than nonsmokers' patients. A positive correlation was noted between age and BASRI-C (r= 0.260, p=0.012). There was no correlation between age at the onset of SpA and structural spine damage. We found a positive correlation between disease duration and the following scores: BASRI-C (r=0.245, p=0.018) and BASRI-S (r=0.274, p=0.003). Patients with non-radiographic axial SpA had lower mSASSS (4.05 vs 12.14; p=0.034), BASRI-s (1.2 vs 4.9; p< 10-3), and BASRI-L (0.42 vs 1.4; p=0.003) than patients with radiographic axial SpA. There was no correlation between the radiographic index and BASDAI and ASDAS-CRP. Conclusion: We confirmed previous observations that male gender, smoking and disease duration are associated with structural damage in the spine [1]. However, CRP and other inflammatory biomarkers were not associated with radiographic evidence of spine involvement. As observed in previous studies, the radiographic spine damage did not correlate with disease activity (BASDAI) [1]. References: [1]Sari I, Haroon N. Radiographic Progression in Ankylosing Spondylitis: From Prognostication to Disease Modification. Curr Rheumatol Rep. 2018 Nov 8;20(12):82. Disclosure of Interests: None declared